EFFECT OF SUPPLEMENTATION OF CAFFEINE ON SPERM MOTILITY AND LIVEABILITY IN MARWARI STALLIONS - KANT, SOURABH; KUMARESAN, YASH PAL; LEGHA, R A; SHARMA, TARU; TALLURI, T R (The Indian Journal of Animal Reproduction, 2023)
Six ejaculates from each three adult stallions were collected via artificial vagina using estrus jenny as dummy. Caffeine was added to semen extender at 0.1, 0.5 and 2 mM during pre-freeze stage and cryopreserved by following standard protocol. The sperm kinetic parameters, membrane functionality and integrity were evaluated with computerassisted sperm analysis, a hypo-osmotic swelling test and epifluorescent microscopy, respectively. The present study revealed that, adding caffeine to stallion semen extender at 0.1, 0.5 and 2 mM levels had positive impact on seminal parameters compared to the control semen. Sperm kinetics (VAP, VSL and STR) and motility were increased in the caffeine treated groups in comparison to the control group. Among these, 2mM caffeine supplemented group the post-thaw sperm motility and other functional attributes have significantly improved compared to the other treatment and control groups.